Revolutionising rapid recovery: a quality improvement project in hip and knee replacement - Rebekah J Parkes; Olusegun Ayeko; Luke Brunton; William Griffiths-Jones; Zsolt Ungvari; Henry Goss (BMJ Open Quality)
With increasing bed pressures and an ageing population, there is a need to increase throughput and reduce the bed burden of joint replacements. These issues were recognised in North Devon and an enhanced recovery pathway was established. Enhanced recovery, which aims to optimise the patient journey and shorten the inpatient admission, was first adopted for hip and knee replacements in North Devon District hospital in 2011. The Rapid Recovery Group, comprised a multidisciplinary team involved in the perioperative patient pathway, formed in the third financial quarter of 2018/2019 (Q3). The group was tasked with the optimisation of the pathway for patients requiring hip and knee replacement from referral to 12 months postoperation. Representatives from the group visited a similar sized hospital with successful outcomes from their pathway in order to compare and then construct a new pathway based on observed practices. Multiple interventions were instigated, alongside continuous data collection, forming a combination of simultaneous and sequential Plan Do Study Act cycles. Interventions involved intraoperative local anaesthetic injection protocols, use of Taurus frames together with nurse-led mobilisation and trials of simplified drug charts. Information collected included type of surgery, length of stay, who mobilised patients and when. Mean length of stay in total hip and knee replacement has dropped from 3.6 to 2.4 days and 3.6 to 2.0 days respectively, comparing mean for the fiscal year 2018/2019 to 2019/2020, putting the hospital in the top 10 trusts in the country. With multiple changes occurring simultaneously, the impact of individual elements is difficult to isolate but the overall impact of the interventions is evident. A drastic improvement in the length of stay has been seen and the collaborative multidisciplinary approach has been pivotal to success.